Men's reproductive health knowledge in Mankweng District, Limpopo Province - Richard M. Rasesemola; Tendani S. Ramukumba; Majapi Masala-Chokwe; Zerish Z. Nkosi (AOSIS, 2017)
Background: Gender roles influence men's attitudes towards reproductive health, and society might assume that reproductive health issues, fertility and family planning are women's responsibilities. Moreover, literature shows that men have insufficient knowledge about reproductive health matters and some misconceptions about modern contraceptive practices. Objectives: The aim of the study was to describe reproductive health knowledge of men in Mankweng District and was conducted in 2015. Methods: A descriptive research study was conducted by using quantitative approach. Data were collected by means of questionnaires. Cluster random multistage sampling was used to select villages in Mankweng District and convenient sampling was used to identify participants who met the inclusion criteria to participate on the study. Results: A total of 200 questionnaires were distributed and returned; 197 (98.5%) of the returned questionnaires were eligible for analysis. The findings indicated that the majority of participants, 74% (n = 145), considered their partners to be unclean during menstruation, and 84.77% (n = 167) of participants did not know how to perform self-testicular examination. More than half of the participants, 55.83% (n = 67), were not in favour of vasectomy and had strong opinions about it; some of those who reportedly knew what a vasectomy involves had some misconceptions. Conclusion: The findings showed that despite participants' reported knowledge about some reproductive health matters their perceptions were unfavourable towards them. Despite men's sufficient knowledge about sexually transmitted infections (STIs) and ways to protect themselves against STIs men had limited knowledge about other male and female reproductive health matters.